Numerical simulation of unsteady flows over a slow-flying bat. Issue 1 (January 2015) - Wang, Shizhao; Zhang, Xing; He, Guowei; Liu, Tianshu
Abstract: This letter describes numerical simulation of the unsteady flow over a slow-flying bat by using the immersed boundary method based on the measured bat wing geometry and kinematics. The main vortical structures around the bat flapping wings are identified, illuminating the lift-generating role of the leading-edge vortices generated mainly in the downstroke. Furthermore, the lift decomposition indicates that the vortex lift has the dominant contribution to the time-averaged lift and the lift associated with the fluid acceleration has the relatively moderate effect.